Producing high quality mung bean sprout using atmospheric cold plasma treatment: better physical appearance and higher γ‐aminobutyric acid (GABA) content. (4th June 2021) - Chou, Yu‐Jou; Cheng, Kuan‐Chen; Hsu, Fu‐Chiun; Wu, James Swi‐Bea; Ting, Yuwen
Abstract: BACKGROUND: Germination of mung beans increases the content of dietary fiber, vitamin C, antioxidants, and γ‐aminobutyric acid (GABA). Atmospheric cold plasma is a recently developed technology that can rapidly modify the surface properties of an object. In this work, atmospheric cold plasma was utilized to promote higher moisture absorption of mung bean seeds and, thus, enhance the germination ratio and GABA level. The selected healthy seeds that were exposed to plasma generated at different ionizing powers. RESULT: According to the experimental results, atmospheric cold plasma treatments on mung bean seeds could induce significantly more water absorption and lead to a higher rate of germination. The physical appearance of the sprout developed after plasma treatment was noticeably modified to a more desirable form, which has a short radicle and longer hypocotyls with a larger diameter. The content of the bioactive component GABA in plasma‐treated beans was approximately three times higher than the untreated group due to the response of seed to the environmental stress created by the plasma treatment. CONCLUSION: The result from this work will serve as a good reference for future investigation that is searching for a solution to enhance bioactive compound production in natural products. © 2021 Society of Chemical Industry.